If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -8 = 2x + 34 Reorder the terms: -8 + 9x = 2x + 34 Reorder the terms: -8 + 9x = 34 + 2x Solving -8 + 9x = 34 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + 9x + -2x = 34 + 2x + -2x Combine like terms: 9x + -2x = 7x -8 + 7x = 34 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + 7x = 34 + 0 -8 + 7x = 34 Add '8' to each side of the equation. -8 + 8 + 7x = 34 + 8 Combine like terms: -8 + 8 = 0 0 + 7x = 34 + 8 7x = 34 + 8 Combine like terms: 34 + 8 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| -2z^2+5z+3=0 | | 3(y-5)+1=2y+34-2y | | -5x-3y-5x-8y= | | -43=-61+x | | 4ay/3d | | (x+y)=80 | | 2x^2-8x-100=20 | | X/27/2 | | x^3-8x^2-33x+26=0 | | 5z-6+6=-36+z | | 9a+2a-8a-3b= | | 29b-93=7 | | 5(2x-10)/2 | | 3x+7=9x+5 | | 4v^2+25v+21=0 | | 16a+8b+1=0 | | 12-b=0 | | (-7b-2c)+(6b-3c-1)= | | X+3x+(x+7)=32 | | 8a(-3a)= | | 50=1.75x | | -((-3)+3)= | | 5x+8=9x-8 | | 16a+8a+1=0 | | b(b-3)=28 | | 0=-16x^2+1400 | | 12=780x | | 6x-46=4x+76 | | 19+1=20 | | 1600=-4x | | 6x+2+3x=74 | | x^4+5x^3+7x^2-4=0 |